On resolving edge colorings in graphs - Varaporn Saenpholphat; Ping Zhang (International Journal of Mathematics and Mathematical Sciences)
We study the relationships between the resolving edge chromatic number and other graphical parameters and provide bounds for the resolving edge chromatic number of a connected graph.